Cognitive semantics and axiology: a new proposal to study metaphor in economics advertising discourse - Cortés de los Ríos, María Enriqueta (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2002)
In this paper, we provide the groundwork for an analysis of metaphor from the point of view of cognitive linguistics. This study attempts to show an interpretation of metaphor which is different from a mere comparison or substitution function and is by no means a deviant or marginal process. We refer to metaphor not only as a matter of language but also as one of thought, that is, in the way we conceptualize one mental domain in terms of another. The specific focus is to analyse the metaphors used in advertising to transfer values to a banking institution. As a result, we aim to demonstrate that cognitive semantics and axiology are closely related.